Comparison of Online and Traditional Basic Life Support Renewal Training Methods for Registered Professional Nurses. Issue 6 (November 2015) - Serwetnyk, Tara M.; Filmore, Kristi; VonBacho, Stephanie; Cole, Robert; Miterko, Cindy; Smith, Caitlin; Smith, Charlene M.
Abstract : Basic Life Support certification for nursing staff is achieved through various training methods. This study compared three American Heart Association training methods for nurses seeking Basic Life Support renewal: a traditional classroom approach and two online options. Findings indicate that online methods for Basic Life Support renewal deliver cost and time savings, while maintaining positive learning outcomes, satisfaction, and confidence level of participants.